Probing the impact of the COVID-19 pandemic on government high school students, Nellore, India - Sulur Anbalagan, Rajalakshmi; Gudugunta Lakshmi, Sreshta; Sowndaram, Chudalai Sankali; Arumugam, Balasubramanian (Frontiers in Education, 2025)
BackgroundThe COVID-19 pandemic is a social and economic crisis and a health issue, which stresses young minds and impacts their academics. Therefore, education during COVID-19 and post-COVID-19 has become a concern. Through this study, we intended to comprehend and explore the academic crisis of high school students and teachers during the pandemic and examine the learning loss after the reopening of schools.MethodsThis research utilized the conservation of resources theory (CoR) as the conceptual framework to explore the internal and external resources involved in the school sector during the COVID-19 outbreak. Researchers employed inductive qualitative study based on the naturalistic approach. The focused group discussions aided in formulating the research design and conducting interviews with 25 teachers and 50 students. These interviews were analyzed using reflexive thematic analysis.ResultsResearchers have extracted six themes, namely COVID-19 academic disruptions/recovery, swaps in lifestyles, teachers’ emotional states, students’ coping mechanisms, systematic mitigation measures and post-COVID-19 recommencements. Among these themes, the swaps in lifestyles theme have sub themes like demanding workload/unemployment, inflation in the economy and academic hindrances. Post COVID-19 recommencement theme consists of three sub-themes: changes in student behavior, compromised education quality, and prevention of spread.ConclusionThese themes show the impact caused by the COVID-19 pandemic on academics and the physical, mental, social and economic health of Nellore's government school students and teachers. Though this qualitative research cannot be generalized, the need for more recovery measures, strategies, policies, programs and funds from the government to deal with the instability resulting from the pandemic needs addressing.